The Movement of Plastic Marine Debris in Indonesian Seas using A Trajectory Model - Engki Andri Kisnarti; Nining Sari Ningsih; Mutiara R. Putri; Nani Hendiarti (Jurnal Segara, 2021)
There are many studies on ocean currents transporting plastic marine debris using hydrodynamic models and trajectories that have been carried out. However, it is still constrained to be applied in Indonesian waters. Therefore, this research aims to obtain the movement patterns of plastic marine debris, influenced by the dynamics of currents in Indonesian waters using hydrodynamic and trajectory models. The methodology used in this research is to use the HAMburg Shelf Ocean Model (HAMSOM) numerical model and the trajectory model. Plastic marine debris is assumed to be conservative particles at sea level with a macro size (2.5 cm-1 m). The particles are released in 6 coastal cities (Manado, Balikpapan, Makassar, DKI Jakarta, Semarang, and Denpasar) at the month and stop at the end month (January, April, July, October). The results showed that particles originating from 6 coastal cities moved along the current to the surrounding areas only, across islands within the Indonesian territory, and even left Indonesian territory.